1989
DOI: 10.2323/jgam.35.233
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Wall Polysaccharides in Coryneform Bacteria

Abstract: From the cell walls of 45 species (14 genera) of coryneform bacteria, we isolated polysaccharides and teichoic acids covalently linked to the peptidoglycan, and examined their chemical composition. Glycerol teichoic acid appeared in strains of the genera Brevibacterium, Pimelobacter, Rarobacter, in all of the species belonging to the "Arthrobacter nicotianae group" of the genus Arthrobacter, and in A, crystallopoietes belonging to the "A. globiformis group." Strains of the genera Rubrobacter, Aureobacterium, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Cell walls were hydrolyzed with 2 N HCl at 100°C for 2 h, dried in vacuo, and then analyzed by the method of Mikami and Ishida (10) by using an HPLC apparatus (model LC-5A; Shimadzu Co., Ltd.) equipped with a Shim-pack ISA 07/S2504 column (250 by 4 mm) and a Shimadzu model RE-530 spectrofluorometer (20). Glycolyl analysis.…”
mentioning
confidence: 99%
“…Cell walls were hydrolyzed with 2 N HCl at 100°C for 2 h, dried in vacuo, and then analyzed by the method of Mikami and Ishida (10) by using an HPLC apparatus (model LC-5A; Shimadzu Co., Ltd.) equipped with a Shim-pack ISA 07/S2504 column (250 by 4 mm) and a Shimadzu model RE-530 spectrofluorometer (20). Glycolyl analysis.…”
mentioning
confidence: 99%
“…The cell wall structures of the cystites differed from those of vegetative cells, and cystites were not produced by the addition of tetracycline at logarithmic and stationary phases. (Takeuchi and Yokota, 1989). Therefore the components of polysaccharides in cell walls would not correlate with cystite formation, and the production of polysaccharides of the cell walls of cystites would have an effect more distinctly on cystite formation and the KOH reaction than the production of peptidoglycans would.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides in crude cell walls were prepared by the sonication-SDS method (Takeuchi and Yokota, 1989). Neutral sugars in polysaccharides were determined by HPLC (Shimadzu LC-10A series, Shimadzu Corp., Kyoto, Japan) with an Asahipak NH2P-50 4E column (4.6ϫ250 mm, Showa Denko K.K., Tokyo, Japan) and an RID-10A detector (Shimadzu Corp.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to clarify whether the sugar compositions of coryneform bacteria are characteristic of the species or not, it was necessary to compare those of many strains belonging to the same species. In the previous study, we analyzed the sugar composition of the polysaccharides obtained from cell walls (12), but in this study, we compared the sugar composition of the cell walls, because it was confirmed that sugar compositions of cell-wall polysaccharides are basically the same as those of cell walls (11).…”
Section: Takeuchimentioning
confidence: 99%